Bridging the Technological Divide Technology Adoption by Firms in Developing Countries - Cirera, Xavier (The World Bank, 2022)
Many of the main problems facing developing countries today and tomorrow--growth, poverty reduction, inequality, food insecurity, job creation, recovery from the COVID-19 pandemic, and adjustment to climate change--hinge on adopting better technology, a key driver of economic development. Access to technology is not enough: firms have to adopt it. Yet it is precisely the uptake of technology that is lagging in many firms in developing countries. Bridging the Technological Divide: Technology Adoption by Firms in Developing Countries helps open the "black box" of technology adoption by firms. The seventh volume in the World Bank Productivity Project series, it will further both research and policy that can be used to support technology adoption by firms in developing countries
Keywords: Climate Change; Coronavirus; Covid-19; Data Analysis; Data Collection; Technology; Technology Adaptation